Redox-Sensitive Transcription Factor NRF2 Enhances Trophoblast Differentiation via Induction of miR-1246 and Aromatase - Muralimanoharan, Sribalasubashini; Kwak, Youn-Tae; Mendelson, Carole R (Endocrinology (Philadelphia), 2018)
Abstract Dysregulation of human trophoblast invasion and differentiation with placental hypoxia can result in preeclampsia, a hypertensive disorder of pregnancy. Herein, we characterized the role and regulation of miR-1246, which is markedly induced during human syncytiotrophoblast differentiation. miR-1246 targets GSK3β and AXIN2, inhibitors of WNT/β-catenin signaling, which is crucial for placental development, and is predicted to target JARID2, which promotes silencing of developmentally regulated genes. Human cytotrophoblasts cultured in 20% O2 spontaneously differentiate to syncytiotrophoblast with induction of hCYP191A/aromatase, a marker of differentiation. miR-1246 was induced >150-fold during syncytiotrophoblast differentiation in 20% O2, whereas targets—GSK3β, AXIN2, and JARID2—were significantly decreased. However, when cytotrophoblasts were cultured in 2% O2, miR-1246 and aromatase induction were prevented. miR-1246 was significantly decreased in placentas of women with severe preeclampsia, whereas AXIN2, GSK3β, and JARID2 were increased, compared with normotensive subjects. To identify factors that regulate miR-1246, we investigated the redox-regulated transcription factor NRF2, which has predicted binding sites in the miR-1246 promoter. Intriguingly, NRF2 messenger RNA was upregulated during syncytiotrophoblast differentiation and significantly reduced by hypoxia and in preeclamptic placentas. Moreover, NRF2 knockdown in cytotrophoblasts inhibited induction of miR-1246 and hCYP19A1, as well as transcription factors C/EBPβ and PPARγ, which are implicated in placental differentiation. Using chromatin immunoprecipitation–quantitative polymerase chain reaction, we found that binding of endogenous NRF2 to the miR-1246 and hCYP191A promoters increased during syncytiotrophoblast differentiation. Thus, NRF2 promotes syncytiotrophoblast differentiation by inducing C/EBPβ, PPARγ, hCYP19A1, and miR-1246, which targets WNT inhibitors and JARID2 and is dysregulated in preeclampsia. NRF2 enhances trophoblast differentiation by upregulating miR-1246 (targets WNT inhibitors), C/EBPβ, PPARγ, and aromatase. NRF2 and miR-1246 are inhibited by hypoxia and dysregulated in preeclampsia.